Tar-Ching Aw, 1948-2017 - Colosio, Claudio (La Medicina del Lavoro, 2017)
I first met Prof. Tar-Ching Aw in Luxembourg in 1994, when he was working as a member of the expert group in charge of the preparation of a EU document on Criteria for Diagnosis and Compensation of Occupational diseases [...]